2019
DOI: 10.3390/ani9020035
|View full text |Cite
|
Sign up to set email alerts
|

Primiparous and Multiparous Sows Have Largely Similar Colostrum and Milk Composition Profiles Throughout Lactation

Abstract: It is important to understand the biological factors influencing the poorer lifetime performance of gilt progeny in comparison to sow progeny and determine whether this may be partially due to differences in lactation performance between primiparous and multiparous sows. It was hypothesized that primiparous sows would have lower levels of immunoglobulin G (IgG) in colostrum and milk compared to multiparous sows, and lower levels of other energetic components. Differences in colostrum and milk composition betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 63 publications
9
24
0
Order By: Relevance
“…The current study found no parity differences in terms of total protein, which is largely consistent with the findings of other authors [ 28 , 29 , 30 ], who all found that protein levels were independent of sow parity. On the other hand, total NFS in colostrum was affected by parity as a result of the values obtained for lactose.…”
Section: Discussionsupporting
confidence: 93%
“…The current study found no parity differences in terms of total protein, which is largely consistent with the findings of other authors [ 28 , 29 , 30 ], who all found that protein levels were independent of sow parity. On the other hand, total NFS in colostrum was affected by parity as a result of the values obtained for lactose.…”
Section: Discussionsupporting
confidence: 93%
“…Lactose quantity is generally considered stable in colostrum and milk. Previous studies did not detect differences in lactose amount among different parities [11,31]. In the present study, the amount of lactose was lower in the fourth-parity sows compared to gilts, which is consistent with a previous report in mature milk [11].…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies did not detect differences in lactose amount among different parities [11,31]. In the present study, the amount of lactose was lower in the fourth-parity sows compared to gilts, which is consistent with a previous report in mature milk [11]. Lactose is generally associated with the total amount of produced and suckled milk, as it is the principal osmotic compound in the mammary secretions [32] and its synthesis by mammary epithelial cells is known to be stimulated by prolactin and inhibited by progesterone.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Progeny born to multiparous sows generally exhibit superior growth performance compared to those born to primiparous sows. However, colostrum and milk composition pro les, are highly similar across parities [6].…”
Section: Discussionmentioning
confidence: 98%